Integrating bioinformatics and experimental validation to reveal a novel VRK score as a prognostic and therapeutic biomarker in hepatocellular carcinoma - Fu, Zhihao; Liu, Dufei; Chen, Menglin; Zhong, Guochao; Zhao, Zhibo; Gong, Junhua; Dai, Xin; Hu, Jiejun; Jia, Degong; Cheng, Lve; Cai, Dong; Gong, Jianping (Frontiers in Immunology, 2025)
BackgroundVaccinia-related kinase (VRK) family genes play a multifunctional role in tumor development. However, the role of VRK family genes in hepatocellular carcinoma (HCC) requires further research. Moreover, the clinical potential of the VRK-related model remains unclear. The aim of this study is to construct a VRK-related model to predict HCC prognosis and therapeutic efficacy.MethodsThe data of HCC patients were extracted from The Cancer Genome Atlas (TCGA), International Cancer Genome Consortium (ICGC), and Gene Expression Omnibus (GEO) databases. The single-sample gene set enrichment analysis (ssGSEA) algorithm was used to calculate the VRK score of each sample. Tumor IMmune Estimation Resource 2.0 (TIMER 2.0) and Tumor Immune Dysfunction and Exclusion (TIDE) were used to evaluate immune cell infiltration and the immune checkpoint response. pRRophetic was used for predicting drug sensitivity. CCK-8, colony formation, wound healing, transwell and xenograft assays were used to experimentally validate the biofunction of VRK2 in HCC.ResultsWe found that all VRK family genes were highly expressed in HCC. Compared with patients with low VRK scores, patients with high VRK1 or VRK2 expression in the TCGA, ICGC, and GSE14520 cohorts had poorer outcomes. Moreover, patients with a high VRK score in the TCGA, ICGC, and GSE14520 cohorts also had poorer outcomes. Importantly, Cox analysis revealed that the VRK score was a potential independent risk factor for HCC. Notably, TIMER2.0 and TIDE suggested that patients with high VRK scores had higher immune checkpoint response rates. Similarly, drug sensitivity analyses suggested that patients with high VRK scores were more resistant to sorafenib, paclitaxel, cisplatin, and gemcitabine. Finally, experimental validation revealed that VRK2 knockdown inhibited HCC development in vitro and in vivo.ConclusionThe VRK score was found to be a reliable indicator for predicting HCC prognosis and therapeutic efficacy. VRK2 is a potential therapeutic target for HCC.